Electrochemical preparation of Cu/Cu2O-Cu(BDC) metal-organic framework electrodes for photoelectrocatalytic reduction of CO2 - Silva, Beatriz Costa E [UNESP]; Irikura, Kallyni [UNESP]; Flor, Jader Barbosa Silva [UNESP]; Dos Santos, Rodrigo Morais Menezes [UNESP]; Lachgar, Abdessadek; Frem, Regina Célia Galvão [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2020)
Thin films of the metal-organic framework (MOF) Cu(BDC) were electrochemically grown by anodic deposition of the ligand 1,4-benzenedicarboxylate (1,4-BDC) on metallic copper to form Cu/Cu2O-Cu(BDC) electrode. The construction of the electrode was optimized by investigating parameters such as current density, time of anodization, and temperature that directly affect its stability and photoactivity. The best performing electrode was prepared when a current density of 2.5mA cm-2 was applied for 6.5min at 110°C. A methanol concentration of 234μmolL-1 was produced from the photoelectron reduction of CO2 under UV-vis irradiation for 3h, an applied potential of +0.10V, and 0.1mol L-1 aqueous sodium sulfate solution saturated with CO2 as supporting electrolyte. The rate of CO2 reduction to methanol was found to be ∼20 times that obtained using Cu/Cu2O electrode alone presumably due to preconcentration of dissolved CO2 in the MOF. The capture of CO2 in the MOF surface and/or cavities was confirmed by ATR and DRIFT spectroscopy.
Keywords: Anodic deposition; CO2reduction; Cu(BDC); MOF electrodes; Photoelectrocatalysis